Co-occurrence between mental distress and poly-drug use: A ten year prospective study of patients from substance abuse treatment. (September 2015) - Burdzovic Andreas, Jasmina; Lauritzen, Grethe; Nordfjærn, Trond
Abstract: Introduction: Longitudinal research investigating psychiatric trajectories among patients with poly-drug use patterns remains relatively scant, even though this specific population is at elevated risk for multiple negative outcomes. The present study examined temporal associations between poly-drug use (i.e. heroin, cannabis, tranquilizers, and amphetamines) and mental distress over a 10-year period. Methods: A clinical cohort of 481 patients was recruited from substance use treatment facilities in Norway, and prospectively interviewed 1, 2, 7 and 10 years after the initial data collection at treatment admission. At each assessment participants completed a questionnaire addressing their substance use and mental distress. Longitudinal growth models were used to examine whether, and if so, how, levels of drug use were associated with the level and rate of change in mental distress over time. Results: Results from the longitudinal growth models showed a co-occurrence between active poly-drug use and mental distress, such that there was a dose–response effect where mental distress increased both in magnitude and over time with the number of drugs used. Reduction in mental distress during the 10-year study period was evident only in the no-drug use condition. Use of multiple drugs and mental distress appear strongly co-related over time. Conclusions: Pre-treatment assessment should carefully identify individuals manifesting poly-drug use and mental disorders. Treatment and follow-up services should be tailored to their specific needs. Highlights: Trajectories of mental health and poly-drug use were examined over 10 years. Elevated poly-drug use was prospectively associated with elevated mental distress. Mental distress systematically increased with a greater number of used drugs. Abstinence from the studied drugs was related to reduced mental distress. Assessment and treatment need to be better tailored to poly-substance users.